How Do Fiscal and Labor Policies in France Affect Inequality? - Espinoza, Raphael (IMF Working Papers; Working Paper ;, 2016)
This paper explores the impact of fiscal and labor market policies on efficiency, inequality, and fiscal outcomes in France. We extend the general equilibrium model calibrated for France by Alla and others (2015), with measures of labor and capital income for different groups in the economy (the unemployed, unskilled workers, skilled workers, public servants). For each of these groups we combine data on the income distribution with the outcomes of policy simulations to assess the impact of a suite of stylized policies on output, the fiscal balance, the Gini coefficient, and the shape of the Lorenz curve. We find that most types of fiscal expansions, while adding to the deficit and debt in the near term, generally reduce inequality, the main exception being capital income tax cuts. A reduction of the minimum wage has an ambiguous impact on the income distribution: the Gini coefficient increases, but the lowest income quintile improves its relative position in the income distribution thanks to positive employment effects. The paper also finds scope for 'win-win' policy packages that could improve overall efficiency, inequality, and fiscal outcomes, for instance if targeted labor tax reductions are offset by cuts in the public wage bill.